Metasubject Competencies in the Expectations of Labor Market Participants - Vesmanov S.V; Zhadko N.V; Vesmanov D.S; Akopyan G.A (Moscow State University of Psychology and Education, 2020)
The article presents results of a study of the opinions of labor market participants regarding the content of metasubject competencies as a component of modern education. The research was conducted by the Project Management Laboratory of MCU in 2019-2020.The study used a qualitative methodology and an in-depth interview tool. Forty-eight respondents representing three groups (managers, specialists and teaching staff of the university) were interviewed. In each group there were respondents working in two enlarged fields: social sciences and natural sciences. Respondents were offered cases describing the main functions of personnel management, and clarifying questions within each case. As a structure for the analysis of metasubject learning outcomes, purposeful actions were developed and proposed, presented in the form of an action, expressed by a verb, and the goal (subject) of the action. A six-step analysis of the data obtained in the course of the study showed that the expectations and perceptions of various labor market participants regarding metasubject learning outcomes in modern schools can be described by nine metasubject competencies: 1) to adapt; 2) to interact; 3) to speak and to write; 4) to achieve; 5) to compete; 6) to present; 7) to design; 8) to manage; 9) to learn. At the practical level, the description of the structure of metasubject competencies in the form of actions and subject areas allowed us to offer end-to-end structural components of educational programs in the school education and to recommend including them in educational standards.